1992
DOI: 10.1136/ard.51.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial dysfunction in ankylosing spondylitis.

Abstract: Subjects were matched for age, sex, height, and weight. There were no echocardiographic differences; however, global nuclide left ventricular function showed several differences between normal volunteers and patients with ankylosing spondylitis. The peak filling rate during exercise was significantly lower in patients with ankylosing spondylitis: normal volunteers 6-5 (SD 1-2); patients with ankylosing spondylitis 5-7 (1-2). The time to reach peak filling during exercise was significantly lower in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 12 publications
0
32
0
2
Order By: Relevance
“…Cardiac and aortic tissue both show intimal proliferation of small arteries (obliterative endarteritis) and fibrosis, similar to that seen around affected joints [64]. Left ventricular filling abnormalities have been described, perhaps resulting from a mild, diffuse increase in interstitial connective tissue without associated inflammatory changes or amyloid deposits [65,66]. Both cardiac and conduction abnormalities and aortic regurgitation occur in patients with various HLA-B27-related extracardiac disorders, regardless of severity.…”
Section: Human Leukocyte Antigen B27-associated Rheumatic Disordersmentioning
confidence: 96%
“…Cardiac and aortic tissue both show intimal proliferation of small arteries (obliterative endarteritis) and fibrosis, similar to that seen around affected joints [64]. Left ventricular filling abnormalities have been described, perhaps resulting from a mild, diffuse increase in interstitial connective tissue without associated inflammatory changes or amyloid deposits [65,66]. Both cardiac and conduction abnormalities and aortic regurgitation occur in patients with various HLA-B27-related extracardiac disorders, regardless of severity.…”
Section: Human Leukocyte Antigen B27-associated Rheumatic Disordersmentioning
confidence: 96%
“…Cardiomyopathy was reported in patients with ankylosing spondylitis 31 years ago already [28]. In a series of studies in such patients with cardiomyopathy, but without aortic regurgitation or conduction abnormalities-other known sequelae of HLA-B27-early diastolic dysfunction was found [29,30] with histological examination showing a mild and diffuse increase in interstitial connective tissue [29]. It was shown that the myocardium can develop histopathological abnormalities in the small arteriesan obliterative intimal proliferation-this obliterative arteritis is also found in the tissues adjacent to affected joints, the sinus node artery, the atrioventricular nodal artery and the vasa vasora of the proximal aorta [2].…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, it has been shown that diastolic dysfunction and left ventricular hypertrophy were seen in patients with AS. Diastolic dysfunction in patients with AS was determined by echocardiography and histopathologic examination (6,7,26).…”
Section: Discussionmentioning
confidence: 99%